The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.3389/fimmu.2017.01041
|View full text |Cite
|
Sign up to set email alerts
|

Dual Face of Vγ9Vδ2-T Cells in Tumor Immunology: Anti- versus Pro-Tumoral Activities

Abstract: Vγ9Vδ2-T cells are considered as potent effector cells for tumor immunotherapy through directly killing tumor cells and indirectly regulating other innate and adaptive immune cells to establish antitumoral immunity. The antitumoral activity of Vγ9Vδ2-T cells is governed by a complicated set of activating and inhibitory cell receptors. In addition, cytokine milieu in tumor microenvironment can also induce the pro-tumoral activities and functional plasticity of Vγ9Vδ2-T cells. Here, we review the anti- versus pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 159 publications
(205 reference statements)
0
42
0
Order By: Relevance
“…21 γδ T cells utilize a variety of surface receptors and cytokines, such as NKG2D, TRAIL, FASL, TNF-α, IFN-γ, Granzyme B, and perforin, to initiate cytotoxicity against cancer cells. [11][12][13]22,23 In addition, given that different subtypes of γδ T cells possess diverse functional signatures, investigations on total γδ T cells in the context of the tumor microenvironment or immunotherapy tend to produce controversial results; for example, there are inconsistent views 24 on the intratumoral γδ T-cell signature as the most favorable prognostic biomarker 25 of cancers and discussions on the pro-and antitumor activities of γδ T cells. 22,26 Nevertheless, Vγ9Vδ2 T cells have promising clinical value and advantages for tumor immunotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…21 γδ T cells utilize a variety of surface receptors and cytokines, such as NKG2D, TRAIL, FASL, TNF-α, IFN-γ, Granzyme B, and perforin, to initiate cytotoxicity against cancer cells. [11][12][13]22,23 In addition, given that different subtypes of γδ T cells possess diverse functional signatures, investigations on total γδ T cells in the context of the tumor microenvironment or immunotherapy tend to produce controversial results; for example, there are inconsistent views 24 on the intratumoral γδ T-cell signature as the most favorable prognostic biomarker 25 of cancers and discussions on the pro-and antitumor activities of γδ T cells. 22,26 Nevertheless, Vγ9Vδ2 T cells have promising clinical value and advantages for tumor immunotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Vδ2 T cells activated by non-peptide phosphoantigens in vitro have been proven to inhibit tumor growth both in vitro and in vivo (40,41). Currently, the results of phase I clinical trials on advanced lung cancer, renal cancer and melanoma have revealed that adoptive Vδ2 T cell transfer therapies have shown certain antitumor effects (42). However, other studies have reported that Vδ2 T cells can also promote tumor progression (43).…”
Section: Discussionmentioning
confidence: 99%
“…However, more recent evidence in colorectal, ovarian and breast cancer has suggested that γδT lymphocytes may also have a pro-tumourigenic role (8)(9)(10). Several reviews over the last few years have described the role of γδT lymphocytes in cancer in general (11)(12)(13)(14)(15), but this review will summarise the evidence to date regarding γδT lymphocytes in breast cancer.…”
Section: The Role Of Gamma Delta T Lymphocytes In Breast Cancer: a Rementioning
confidence: 99%